Liana: a decentralized load-dependent scheduler for performance-cost optimization of grid service - Liu, Dan; Cao, Yuan-Da; Li, Chun-Qing (The Journal of supercomputing, 2009)
This paper addresses the scheduling problem in decentralized grid systems. Such problem focuses on computing a large set of arbitrary tasks to optimize the system performance while minimizing the average system costs. The mainstream solution flourished in recent literatures is to maximize the total system throughput by modeling such systems in either a network flow or a tree. However, most of them neglect the movements of tasks and load-dependent system costs which, in fact, are crucial to the system performance in real situations. In this paper, a Service-Oriented Overlay Network (SOON) is presented, in which the service nodes encapsulate both computation and communication resources and the links are used to track the movements of tasks instead of describing communication. An analytical Cost-Charge (C 2 ) model, in which both running cost and service charge are dependent on load, is proposed to describe the problem by incorporating degree-dependent task allocation into a closed queuing network model. The Infinitesimal Perturbation Analysis (IPA) is applied to solve C 2 theoretically. Following the theoretical analysis, a scalable decentralized scheduler named Liana (the movements of tasks in the proposed system like the growth and spread of evergreen liana, so we use Liana to name the proposed scheduler) is proposed. The major components of Liana are an autonomous scheduling algorithm and a Degree-Driven Protocol (DDP). Furthermore, trace based simulations on the test bed distributed widely across the world are implemented to compare the system performance by Liana with recent approaches. The proposed approach shows promising results that the close-to-optimal service utilization is achieved when taking system cost into account.